Podcast: Basics of Knee Radiographs - Claire Sandstrom (Association of American Medical Colleges, 2013)
Abstract Short podcast (<15 minutes) on the Basics of Knee Radiography in the setting of trauma or acute knee pain in the Emergency Department. Topics include normal radiographic views, normal anatomy, and evaluation of the suprapatellar recess. Target audience is junior-level radiology residents and medical students and non-radiology residents on Radiology rotations. Senior radiology residents, practicing general radiologists, and non-radiologist physicians may also find the podcast informative. The podcast is small enough (19.1 MB) that it could be distributed as an attachment by our university email; alternatively, it could be posted in a central location and downloaded or played online. The residents were sent the podcast 5 days prior to attending a noon conference on Knee Trauma, with instructions to download and watch it at least once but encouraged to watch as many times as desired to feel confortable with the material. Most residents reported spending 20-30 minutes in total watching the podcast. After attending the conference, they were asked to complete an anonymous survey, the results of which are given below. Nine of 10 residents responded. Three were in their first month of radiology residency, while the remaining six had completed at least one year of residency. All reviewed the podcast once or twice prior to conference; most (6) reported watching it through continuously, and the rest (3) rewound multiple times to chapters of interest. Eight respondents reported the level of the material as "just right for where I am right now"; 1 entering the final year of residency reported that the podcast was, "Pretty basic but I learned at least one thing." All of the respondents reported that the podcast improved their understanding of, and ability to engage in, the subsequent conference material. Specific comments included: "I think podcasts are great. I have always utilized them because I can store them on my tablet and watch on the go without needing an internet connection. I really like the ones with images that are color coded and highlighted and with simple explanations." "Definitely. This is great because I'm not good at auditory learning, and I can go back and rewatch sections with a book in front of me until I understand. This is fantastic!" "Excellent way to make conference time more efficient." "I think it's a very effective tool. For junior residents, it provides a fighting chance to get value out of the cases when they lack enough prior exposure to make sense of them. For seniors, it allows them to quickly look for gaps in their knowledge. For all, it allows periodic review when a question comes up... 'What was that thing I learned again during [that] lecture'" Residents were also given the opportunity to rate, as well as raise concerns or suggest changes, to different aspects of the podcast. They all reported Excellent (no issue) or Good (minor issues) with the podcast slide layout, text size, and annotations, with audio quality, sound level, and narrative speed, and with length, clarity, and accuracy of content. The same was true for Image quality except that one respondent answered "Average, could be improved" due to difficulty in seeing the soft tissue differentiation on the slides discussing fat pads.